The anatomy of the euro area interest rate swap market - Silvia Dalla Fontana; Marco Holz auf der Heide; Loriana Pelizzon; Martin Scheicher (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2019)
Using a novel regulatory dataset of fully identified derivatives transactions, this paper provides the first comprehensive analysis of the structure of the euro area interest rate swap (IRS) market after the start of the mandatory clearing obligation. Our dataset contains 1.7 million bilateral IRS transactions of banks and non-banks. Our key results are as follows: 1) The euro area IRS market is highly standardised and concentrated around the group of the G16 Dealers but also around a significant group of core "intermediaries"(and major CCPs). 2) Banks are active in all segments of the IRS euro market, whereas non-banks are often specialised. 3) When using relative net exposures as a proxy for the "flow of risk" in the IRS market, we find that risk absorption takes place in the core as well as the periphery of the network but in absolute terms the risk absorption is largely at the core. 4) Among the Basel III capital and liquidity ratios, the leverage ratio plays a key role in determining a bank's IRS trading activity.
urn:nbn:de:hebis:30:3-509232
Keywords: G21; E43; E44; 330; derivatives; network analysis; interest rate risk; banking; risk management; hedging